Anaerobic Digester Optimization Using Extremum Seeking and Model-Based Algorithms. A Comparative Study. Issue 1 (July 2017) - Caraman, S.; Barbu, M.; Ifrim, G.; Titica, M.; Ceanga, E.
Abstract: The paper deals with the optimization of an anaerobic digester with respect to a performance criterion which targets the maximization of the methane production. It is penalized by the environment pollution with the discharged water. The paper includes a comparative study regarding the performances of two optimization approaches: the extremum seeking control, in stochastic and deterministic versions, and the model-based control respectively. The latter uses a characteristic of the optimal regimes which supplies the optimal setpoint (the dilution rate) as a function of the substrate concentration in the inflow, estimated by an extended Kalman filter.